MARKET REACTIONS TO BOYCOTT ANNOUNCEMENTS: ANALYZING THE IMPACT ON TARGETED COMPANIES IN INDONESIA - Avianuari, Fanny; Hendranastiti, Nur Dhani (International Journal of Social Service and Research, 2024)
This research aims to examine the changes in abnormal returns (AR) and trading volume activity (TVA) before and after the announcement of MUI Fatwa Number 83 of 2023, which targets companies for boycott due to their alleged affiliation with Israel. This study employed an event study approach, using a 5-day event window, 10-day event window, 20-day event window and 30-day event window before and after the Fatwa's announcement to measure abnormal returns and trading volume activity. The analysis began by examining the normality of the data to determine whether it was normally distributed. For normally distributed data, a Paired Sample T-test was used, while the Wilcoxon Signed Rank test was applied to non-normally distributed data. The analysis reveals a significant difference in AR during the initial 5-day window, indicating a strong short-term market reaction driven by investor sentiment and uncertainty. However, for longer windows (10, 20, and 30 days), no significant differences in AR were found, suggesting that the market stabilized as new information was absorbed, consistent with the Efficient Market Hypothesis (EMH) by Eugene Fama (1970). Conversely, TVA showed significant increases across all event windows, indicating sustained investor interest and heightened trading activity. This suggests that while the impact on stock prices was short-lived, the boycott had a lasting influence on trading volume, reflecting continued portfolio adjustments.